Compact ultra-wideband metamaterial antenna - Alhawari, Adam Reda Hasan; Ismail, Alyani; Mahdi, Mohd Adzir (IEEE, 2010)
A negative index metamaterial antenna is presented in this paper for ultra-wideband (UWB) applications; which operates in C and X-bands. The proposed antenna is composed of three-unit cells of left-handed metamaterial (LHM) where these LHM unit cells are composed of a combination of modified octagonal spiral resonator (OSR), octagonal split-ring resonator (OSRR), capacitance-loaded strip (CLS), and wire that exhibit negative electrical permittivity (ε) and negative magnetic permeability (μ) simultaneously. A trident-shaped feeding strip is used to feed all the three LHM unit cells respectively; which are united into a single line feeding strip on top of substrate surface, whereas the wire and ground plane are deposited in the bottom of substrate surface. By using of these techniques, we were able to produce an antenna solely from metamaterial that is for the first time used in antenna design. Return loss simulation showed that this antenna achieves 94% bandwidth for VSWR < 2 over the frequency band of 4.8-13.4 GHz, with a maximum gain of 2.7 at 11 GHz. The far-field radiation patterns, which show good Omnidirectional performance, are also discussed here.